PENGARUH KINERJA LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA MASKAPAI PENERBANGAN PT. LION AIR DI PEKANBARU - Kirana Feri; Alwie Furwanti Alvi; Rahayu Danar Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The Study aims to determine the effect of service performance and price perception on costumer satisfaction and costumer loyalty on PT. Lion Air in Pekanbaru. The population in this study include costumer who use the service on PT. Lion Air in pekanbaru, totaling 112 people. The sample was determined by using purposive sampling method. In this study the sample studied used a questionnaire as an instrument to prove the results of the study, for testing the hypothesis in the study using the path analysis method (path analysis) with the help of the SPSS program. The results show that: 1) there is a significant effect of service performance on customer satisfaction on Lion Air Airlines in Pekanbaru, 2) there is a significant effect on perceived price on customer satisfaction on Lion Air Airlines in Pekanbaru, 3) there is a significant effect on service performance on customer loyalty on Lion Air Airlines in Pekanbaru, 4) there is a significant effect on perceived price on customer loyalty on Lion Air Airlines in Pekanbaru, 5) there is a significant effect on customer satisfaction on customer loyalty on Lion Air Airlines in Pekanbaru, 6) there is a direct and significant influence on customer loyalty through customer satisfaction on Lion Air Airlines in Pekanbaru, 7) there is an indirect and significant influence on customer loyalty through customer satisfaction on Lion Air Airlines in Pekanbaru.Keywords: Service Performance, Price Perception, Costumer Satisfaction, Costumer Loyalty.